As fronteiras do acesso à justiça - Montes, Priscila Silva [UNESP] (2014)
The present work aims to diagnose the reasons why the right to judicial access is diminished to those in structural poverty situation. In this way, it departs from the frontiers, i.e., from the limits which separate two universes: one is conceived to orientate order and knowledge; the other one to be marginalized immediately. It was decided by the side occupied by the oppressed individuals, represented by the colonized societies in a global scope and the environment where those oppressed live in, exiled from human conditions in a local community. Initially guided by the Extreme Poverty and Human Rights Commission report by the UNDP, we point out eight possible judicial access frontiers. Yet, there are clues that those would be only detachments from a larger frontier, which could only be analyzed by going back in past and seeking the comprehension of how factors of internal and external domination act towards the consolidation of underdevelopment, dependent capitalism, competitive order and, subsequently, for the social classes disparity. It is know that Brazil has singularities that do not permit the immediate adoption of theories and solutions which are effective abroad. Finally, this work intends to analyze how these factors act on the judicial access problematic - which creates then a barrier that prevents the democratic order and deny the right to citizenship to many individuals